Secondary infections worsen the outcome of COVID‐19 in patients with hematological malignancies: A report from the ITA‐HEMA‐COV. Issue 5 (12th August 2022) - Zappasodi, Patrizia; Cattaneo, Chiara; Valeria Ferretti, Virginia; Mina, Roberto; José María Ferreri, Andrés; Merli, Francesco; Oberti, Margherita; Krampera, Mauro; Romano, Alessandra; Zerbi, Caterina; Ferrari, Jacqueline; Cavo, Michele; et al.
Abstract: The impact of secondary infections (SI) on COVID‐19 outcome in patients with hematological malignancies (HM) is scarcely documented. To evaluate incidence, clinical characteristics, and outcome of SI, we analyzed the microbiologically documented SI in a large multicenter cohort of adult HM patients with COVID‐19. Among 1741 HM patients with COVID‐19, 134 (7.7%) had 185 SI, with a 1‐month cumulative incidence of 5%. Median time between COVID‐19 diagnosis and SI was 16 days (IQR: 5–36). Acute myeloid leukemia (AML) and lymphoma/plasma cell neoplasms (PCN) were more frequent diagnoses in SI patients compared to patients without SI (AML: 14.9% vs. 7.1%; lymphoma/PCN 71.7% vs. 65.3%). Patients with SI were older (median age 70 vs. 66 years, p  = 0.002), with more comorbidities (median Charlson Comorbidity Index 5 vs. 4, p  < 0.001), higher frequency of critical COVID‐19 (19.5% vs. 11.5%, p  = 0.046), and more frequently not in complete remission (75% vs. 64.7% p  = 0.024). Blood and bronchoalveolar lavage were the main sites of isolation for SI. Etiology of infections was bacterial in 80% ( n  = 148) of cases, mycotic in 9.7% ( n  = 18) and viral in 10.3% ( n  = 19); polymicrobial infections were observed in 24 patients (18%). Escherichia coli represented most of Gram‐negative isolates (18.9%), while coagulase‐negative Staphylococci were the most frequent among Gram‐positive (14.2%). The 30‐day mortality of patients with SI was higher when compared to patients without SI (69% vs. 15%, p  < 0.001). The occurrence of SI worsened COVID‐19 outcome in HM patients. Timely diagnosis and adequate management should be considered to improve their prognosis.